Is there a difference by sex in simple reaction time and impulsivity in Junior Brazilian Judo Team athletes? - Ferreira, T.; Noce, F.; Costa, I.; Vieira, M.; Costa, V. (Archives of Budo Science of Martial Arts and Extreme Sports, 2017)
Background & Study Aim: The simple reaction time and impulsivity are variables that contribute to the athlete`s performance in combat sports. However, little is known about the behaviour of these two variables in relation to elite athletes in judo. Thus, the aim of this study was to knowledge whether there was a difference in simple reaction time and impulsivity in athletes of the Junior Brazilian Judo Team from different sexes.